Improving the Performance of the Army Planning and Budget Staff at the Army Headquarters Through the Implementation of a Planning Information System - Oviyan Patra; Laurensius Chrisma; Evan Nugraha; Hendy Suryana (Green Publisher Indonesia, 2026)
This study aims to analyze the relationship between technology, organization, and human resources variables and the effectiveness of the Planning Information System (SISFOREN) usage at the Army Headquarters (MABESAD), assess the impact of SISFOREN effectiveness on the performance of the planning department, and identify obstacles faced during implementation. A quantitative approach using the Technology Acceptance Model (TAM) was employed, with data collected through structured surveys distributed to planning and budgeting staff members. The findings reveal that technology does not significantly influence effectiveness (), attributed to implementation challenges and users' limited technical understanding. In contrast, organization positively impacts effectiveness (), highlighting the importance of structured communication and organizational support. Human resources also significantly affect effectiveness (), emphasizing the critical need for comprehensive training programs. Furthermore, the effectiveness of SISFOREN significantly enhances planning performance (), demonstrating improvements in data monitoring, decision-making speed, and administrative efficiency. However, obstacles such as inadequate technology integration, user skill gaps, and unsupportive organizational structures persist. The study contributes to understanding information system implementation in military contexts and provides practical recommendations for optimizing SISFOREN's deployment. Addressing these identified issues is essential for maximizing SISFOREN's implementation success and improving its overall efficiency in supporting the Indonesian Army's planning and budgeting operations.